Radar efficiency and the calculation of decade-long PMSE backscatter cross-section for the Resolute Bay VHF radar - Swarnalingam, N.; Hocking, W. K.; Argall, P. S. (Annales Geophysicae, 2009)
The Resolute Bay VHF radar, located in Nunavut, Canada (75.0° N, 95.0° W) and operating at 51.5 MHz, has been used to investigate Polar Mesosphere Summer Echoes (PMSE) since 1997. PMSE are a unique form of strong coherent radar echoes, and their understanding has been a challenge to the scientific community since their discovery more than three decades ago. While other high latitude radars have recorded strong levels of PMSE activities, the Resolute Bay radar has observed relatively lower levels of PMSE strengths. In order to derive absolute measurements of PMSE strength at this site, a technique is developed to determine the radar efficiency using cosmic (sky) noise variations along with the help of a calibrated noise source. VHF radars are only rarely calibrated, but determination of efficiency is even less common. Here we emphasize the importance of efficiency for determination of cross-section measurements. The significant advantage of this method is that it can be directly applied to any MST radar system anywhere in the world as long as the sky noise variations are known. The radar efficiencies for two on-site radars at Resolute Bay are determined. PMSE backscatter cross-section is estimated, and decade-long PMSE strength variations at this location are investigated. It was noticed that the median of the backscatter cross-section distribution remains relatively unchanged, but over the years a great level of variability occurs in the high power tail of the distribution.